2016
DOI: 10.1016/j.ijwd.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal rejuvenation using energy-based devices

Abstract: Physiologic changes in a woman’s life, such as childbirth, weight fluctuations, and hormonal changes due to aging and menopause, may alter the laxity of the vaginal canal, damage the pelvic floor, and devitalize the mucosal tone of the vaginal wall. These events often lead to the development of genitourinary conditions such as stress urinary incontinence; vaginal atrophy; dryness; and physiologic distress affecting a woman’s quality of life, self-confidence, and sexuality. Various treatment modalities are curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
80
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 27 publications
0
80
0
1
Order By: Relevance
“…3 Recently, different studies suggested promising short-term results with treating vaginal laxity using energy-based devices such as lasers and low-dose radiofrequency. 5,6 In the present study, we aimed to retrospectively extract and analyze the safety and efficacy data of the nonablative Er:YAG IntimaLase treatments performed in our clinical practice during a 2.5-year period. The results of our retrospective case series indicate that the nonablative Er:YAG laser produced favorable results without serious adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Recently, different studies suggested promising short-term results with treating vaginal laxity using energy-based devices such as lasers and low-dose radiofrequency. 5,6 In the present study, we aimed to retrospectively extract and analyze the safety and efficacy data of the nonablative Er:YAG IntimaLase treatments performed in our clinical practice during a 2.5-year period. The results of our retrospective case series indicate that the nonablative Er:YAG laser produced favorable results without serious adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, new energy deviceebased therapies have become available, including radiofrequency, high-focused ultrasound, and different laser therapies. 5,6 These methods are minimally invasive and offer better efficiency than traditional noninvasive methods. 2 different laser technologies have been proposed to treat genitourinary problems-microablative fractional CO 2 lasers and Er:YAG lasers.…”
Section: Introductionmentioning
confidence: 99%
“…and the patients can resume their usual activities the same day. In 2015, the results of treatment of vulvovaginal laxity, sexual dysfunction and mild to moderate stress urinary incontinence with RF-based device, were published [50]. This prospective study involved 23 women including 6 premenopausal and 5 menopausal.…”
Section: Radio-frequency Devicesmentioning
confidence: 99%
“…The noninvasive treatments may also be performed by fractional carbon dioxide laser, non‐ablative laser, monopolar radiofrequency devices, hyaluronic acid fillers, and fat transplantation (Karcher & Sadick, ).…”
mentioning
confidence: 99%
“…The noninvasive treatments may also be performed by fractional carbon dioxide laser, non-ablative laser, monopolar radiofrequency devices, hyaluronic acid fillers, and fat transplantation (Karcher & Sadick, 2016). Some studies aimed to quantify the intensity of vulvovaginal symptoms before and after treatment with high molecular weight HA, to test the tolerability and safety of the product, to evaluate the effect on the quality of life and the compliance to the treatment (Chen et al, 2013).…”
mentioning
confidence: 99%